Anisotropic Magnetoresistance Effect of Intercalated Ferromagnet FeTa3S6 - Miao, Ying-Qing; Guo, Jun-Jie; Luo, Zi-Yan; Zhong, Mian-Zeng; Li, Bo; Wang, Xi-Guang; Nie, Yao-Zhuang; Xia, Qing-Lin; Guo, Guang-Hua (Frontiers in Physics, 2022)
Intercalated transition metal dichalcogenides have been widely used to study the magnetic and magnetoelectric transport properties in a strong anisotropic and spin-orbit coupling environments. In this paper, ferromagnetic FeTa3S6 (also known as Fe1/3TaS2) single crystals were grown by the chemical vapor transport method, and its magnetic and magnetoelectric transport properties were measured. The results show that FeTa3S6 has ferromagnetic ordered below 37K, with sharp switching of magnetization, butterfly-shaped double-peak magnetoresistance and anomalous Hall effect, and the magnetization and resistance have strong anisotropy. When magnetic field oriented parallel to the c-axis, the magnetoresistance exceeds 10% at the temperature of 10K, and negative magnetoresistance is generated when the magnetic field is larger than the switching field. When the direction of the magnetic field of 9T rotates from out-of-plane to in-plane, the anisotropic magnetoresistance exceeds 40%, the angle-dependent Hall resistance presents a novel trend, which may be due to the existence of topological Hall effect or other magnetic structures in the FeTa3S6 thin film. When the magnetic field of 9T rotates in the ab-plane of the sample, the in-plane anisotropic magnetoresistance conforms to the form of cos2φ. The experimental results in this paper provide important information for the study of the magnetic and magnetoelectric transport properties of intercalated transition metal dichalcogenides.